Ancestral Shuar knowledge and the conservation of amazonian palms: toward the creation of resilient biohabitats in the neotropics (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
The progressive disappearance of ancestral construction techniques in the Amazon represents a threat both to the cultural continuity of Indigenous peoples and to the conservation of key plant species used in vernacular architecture. This study aimed to recover and apply the construction knowledge of the Shuar people, with emphasis on roof weaving using local palm species, highlighting its potential in creating sustainable habitats that promote the active conservation of biodiversity. The research was carried out within the framework of the Amazonian Vernacular Architecture Seminar at Ikiam University, as the culmination of a theoretical-practical training process. A prototype, scenario was built as a contemporary reinterpretation of Shuar architecture, guided by a master weaver from the Kuamar community (Morona Santiago), using Attalea butyracea, Carludovica palmata, and Iriartea deltoidea over a bamboo structure. The results showed that the roofs exhibited excellent thermal and waterproof performance while strengthening the intergenerational transmission of knowledge and the active conservation of species. In conclusion, the integration of this knowledge into contemporary architecture represents an effective strategy to connect biodiversity, sustainability, and culture.